Progress and opportunities of doubled haploid production - Asif, Muhammad (SpringerBriefs in Plant Science, 2013)
Deals with the historical perspectives and the current status of doubled haploid production along with its practical implications in basic and applied research. It highlights various haploid production methods with a comprehensive discussion on their pros and cons, bottlenecks, and embryogenic pathways. The review also describes in detail the results of molecular and genomic studies conducted to investigate the underlying principles of this spectacular technique that has changed the status of many species from recalcitrant to responsive over the last ninety years.